Causes of bile thickening and its relationship with breakfast consumption among students of the school of Mongolian University of Pharmaceutical Sciences - Tsogt-Ochir, Munkh-Ochir; Battsengel, Odonchimeg; Tudev, Ariunjargal (Journal of Eastern - Western Pharmacology and Pharmacy, 2025)
Mongolian Traditional medicine has a history of more than 5000 years, and it is our insparable heritage created by the life experiences of the Mongolian ancestors. One of the cultural heritages of Mongolians is the culture of eating and drinking, which is basis of disease prevention, health care, and healthy living, according to the characteristics of the body, the place where they live, and the time and season. There are several causes of thickening of bile / coagulation /, among which not having breakfast is regurlarly is the most common cause. Breakfast not only gives a person energy and energy for the day, but also affects and concentration, so it is important to use it regularly and make it a habit.